Bibliometric Analysis of Entrepreneurship Education: Trends and Research Gaps - Muh. Ihsan Said Ahmad; Ferry Arfiansyah (West Science Journal Economic and Entrepreneurship, 2024)
This study presents a bibliometric analysis of entrepreneurship education, examining research trends, publication patterns, and global collaborations from 2000 to 2024. Utilizing data from Scopus, the analysis identifies key thematic clusters within the field, such as foundational pedagogical approaches and the integration of technological advancements in educational practices. The research highlights significant shifts towards experiential and technology-enhanced learning, reflecting the evolving demands of the entrepreneurial landscape. Visualization tools like VOSviewer facilitated the exploration of global collaborative networks, revealing robust interconnections among researchers worldwide with a notable focus in regions such as North America, Europe, and Asia. The analysis also depicts a pronounced increase in research output post-2012, suggesting a burgeoning interest and recognition of entrepreneurship education's critical role in economic development. The findings underscore the importance of adaptability in educational policies and practices to foster effective entrepreneurial training. This study not only maps the intellectual structure of entrepreneurship education but also provides insights into the dynamic nature of research collaborations that shape the field.